Students and privacy in the networked environment - Banek Zorica, Mihaela (Array, 2011)
The continuing adoption of new emerging technologies is not only changing the educational environment but also raises concerns in terms of students’ digital media literacy and their sense of privacy in online environments. Despite the widespread agreement of its importance the lack of formal training in information and media literacy across the curriculum actually forces students to acquire necessary skills through informal learning. This lack of systematic education potentially leads to differences in student competencies. Authors present the results of the study on students’ attitude towards information privacy their private online environment (inside their chosen social network), as well as their professional environment (inside their e-learning system). The research was conducted in December of 2010 where a total of 397 students from the Faculty of Humanities and Social Sciences (FHSS) at the University of Zagreb and Accredited College of Business and Management "Baltazar Adam Krčelić" (ACBM) responded to an online survey. The results showed significant differences between the samples, where the students from FHSS were more aware of the importance of protecting their private data inside their social network, as well as inside their educational environment. The study confirmed the original assumption that the lack of formal guidance through student education resulted in significant differences between the students.